Implementasi Supervisi Pada Pembelajaran Online Standar Kompetensi Lulusan Bahasa Asing Mahasiswa di Pusat Pengembangan Bahasa UIN Raden Mas Said Surakarta - Yetty ulfah (Improvement: Jurnal Ilmiah untuk Peningkatan Mutu Manajemen Pendidikan, 2021)
Educational supervision is one of the efforts to develop or improve the quality at every level and type of education, including formal and non-formal education in a national education system. This research aims to investigate 1) the supervision model in learning the Graduate Competency Standard (SKL) for students at the Language Development Center at UIN Raden Mas Said Surakarta, 2) the goals and functions of supervision, 3) barriers, and 4) solutions to the barriers in supervision. This research was descriptive qualitative research conducted at online learning during the pandemic of covid 19. The results of this study reveal that 1) the model used is..a clinical supervision model, 2) the purpose of the supervision activity implementation is to determine the course of SKL learning, while the function of the activity is to improve the learning situation and atmosphere through the professional development of tutors, 3) obstacles in the implementation of supervision generally come from tutors and some are from students, 4) solutions to these obstacles are also given significantly to both parties, tutors and students. Keywords: Supervision, Online Learning, Graduate Competency Standard